When past meets future in Persian: A construction grammar approach to futurity. Issue 2 (3rd April 2022) - Mousavi, S. Hamzeh
ABSTRACT: In Persian, two of the verbal constructions used for expressing futurity – the Past Simple and the Future Simple – are built around the past form of the main verb. This paper seeks to demystify this connection between the past and the future by investigating how these past forms contribute to the expression of futurity and setting this within an overall analysis of the future constructions in this language. Based on the form of the main verb in 940 sentences with verbal future constructions, six constructions were identified and categorized into future-oriented past constructions (FPST), which include the Past Simple and the Future Simple, and future-oriented present constructions (FPRT), which include the Present Simple, the Present Progressive, the Present Subjunctive and the WANT construction. A construction grammar approach together with Reichenbach and neo-Reichenbach terminology was then utilized to distinguish the differing relations between tense, aspect, mood and speaker perspective, and assign syntactic-semantic maps in terms of features such as level of formality, perfectness, intended future, certainty and inner aspect (aktionsart) to each of the FPST and FPRT constructions. It is argued that the use of the past form of the main verb in the Past Simple and the Future Simple (FPST constructions) owes much to aspectual and ontological factors, with the past element indicating certainty, perfectness and a speaker perspective of looking back.